Experimental investigation on the flexural behavior of concrete reinforced by various types of steel fibers - Zhao, Liangping; Chen, Gang; Huang, Chunshui (Frontiers in Materials, 2023)
The benefit of steel fiber on the mechanical behaviors of concrete has been well accepted. The flexural behavior of steel fiber reinforced concrete (SFRC) is complicated which depends on many factors, such as matrix properties, fiber material properties, fiber geometries, fiber volume contents, and interface properties. Thus, the investigations on the flexural behavior of SFRC are needed to be expanded. In this study, the effects of fiber type with varying shapes and aspect ratios on the flexural performance of SFRC were investigated. Five steel fibers were adopted in this study: milled fiber (M), corrugated fiber (C) and three hooked fibers with aspect radios of 45 (HA), 55 (HB), and 65 (HC). Two volume fractions (0.4% and 1.0%) of steel fiber and two compressive strengths (normal and high strengths) of matrix were considered. The load-deflection curves, energy absorption capacity and equivalent flexural strength were discussed. The results show that the flexural behavior of SFRC beams reinforced by 1.0% fibers is significantly higher than that of the beams reinforced by 0.4% fibers. Hooked fiber reinforced beams performed the best flexural load-deflection response compared to the beams reinforced by milled fiber and corrugated fiber reinforced, and exhibited an increasing trend of flexural performance as the fiber aspect ratio increased. The differences between specimens with different fibers for high strength matrix are more obvious compared to the normal strength matrix.